IMPLEMENTASI PROGRAM GERAKAN LITERASI “LEMBAR IKAL LA KARAMAT” DI SDIT INSAN KAMIL SANTI KOTA BIMA - Maulidia Khairunisah; Syarifuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objective of this research is to describe the implementation of a literacy movement program named "Lembar Ikal La Karamat" within the context of elementary education, specifically at SDIT Insan Kamil Santi in Bima City. As one of the driving schools in Bima City, SDIT Insan Kamil implements various innovative programs, one of which is the "Lembar Ikal La Karamat" program. This program translates to "Reading together with Insan Kamil, 'Sakola Karawi Ma Taho'," which means Insan Kamil school that does good things. The program is implemented in stages through reading, writing, and group discussion activities every Thursday morning for 30 minutes before teaching and learning activities take place in the classroom. It is expected to enhance students' reading interest and achievement. This research employs a qualitative method with a descriptive approach to understand how the "Lembar Ikal La Karamat" literacy movement program is carried out at SDIT Insan Kamil and its impact on students. Data collection was conducted through observation of teacher and student activities during the "Lembar" program implementation, interviews with the principal, the teacher coordinating the "Lembar" activities, and students. Documentation was also carried out during the "Lembar" activity process. The research results indicate that the implementation of the "Lembar Ikal La Karamat" literacy movement program makes a positive contribution to students' reading interest and achievement. The majority of students have reached the minimum competency threshold for reading literacy, resulting in a significant increase in the Literacy score on their education report cards, with a sector change of up to 6.67 from the previous year.